THE CRYSTALLOGRAPHIC FABRIC AND TEXTURE OF SIDERITE IN CONCRETIONS: IMPLICATIONS FOR SIDERITE NUCLEATION AND GROWTH PROCESSES - Hounslow M.W. (My University, 2001)
The crystallographic fabric of siderite in siderite concretions has been determined for upper Carboniferous (Westphalian-A) non-marine concretions and lower Jurassic (Pliensbachian) marine concretions. Compositional zoning indicates that individual siderite crystals grew over a period of changing pore water chemistry, consistent with the concretions being initially a diffuse patch of cement, which grew progressively. The siderite crystallographic fabric was analysed using the anisotropy of magnetic susceptibility, which is carried by paramagnetic siderite. The siderite concretions from marine and non-marine formations exhibit differences in fabric style, although both display increases in the degree of preferred siderite c-axis orientation towards the concretion margins. The Westphalian non-marine siderites show a preferred orientation of siderite c-axes in the bedding plane, whereas the Pliensbachian marine siderites have a preferred orientation of c-axes perpendicular to the bedding. In addition, a single marine concretion shows evidence of earlier formed, inclined girdle-type fabrics, which are intergrown with later formed vertical c-axis siderite fabrics. The marine and non-marine fabrics are both apparently controlled by substrate processes at the site of nucleation, which was probably clay mineral surfaces. Siderite nucleation processes on the substrate were most probably controlled by the (bio?) chemistry of the pore waters, which altered the morphology and crystallographic orientation of the forming carbonate. The preferred crystallographic orientation of siderite results from the orientation of the nucleation substrate. Fabric changes across the concretions partially mimic the progressive compaction-induced alignment of the clay substrates, while the concretion grew during burial.
Keywords: CONCRETIONS; FABRIC; MAGNETIC SIDERITE; SUBSTRATE; SUSCEPTIBILITY; Jurassic; Carboniferous; Pliensbachian; Mesozoic::Jurassic::Lower::Pliensbachian; Палеозой::Каменноугольная; Mesozoic::Jurassic; Paleozoic::Carboniferous; Мезозой::Юрская; Мезозой::Юрская::Нижний::Плинсбахский